Parasitic Contamination of Fruits and Vegetables Collected from Local Markets of Bahir Dar City, Northwest Ethiopia - Alemu G; Nega M; Alemu M (Research and Reports in Tropical Medicine, 2020)
Getaneh Alemu,1 Mezgebu Nega,2 Megbaru Alemu1 1Department of Medical Laboratory Science, Bahir Dar University, Bahir Dar, Ethiopia; 2Department of Medical Parasitology, Felegehiwot Comprehensive Specialized Hospital, Bahir Dar, EthiopiaCorrespondence: Getaneh Alemu Tel +25 192 284 2776Email getanehmlt@gmail.comBackground: Fruits and vegetables, which are consumed raw, act as potential sources for the spread of various parasitic diseases. The rate of contamination and species of contaminant parasites varies based on climatic, ecological, and human factors. Therefore, local data about the contamination status and predisposing factors augments efforts for successful control of parasitic diseases.Methods: A cross-sectional study was conducted on fruits and vegetables collected from local markets of Bahir Dar city from February to May 2019. A total of 384 samples were purchased from three randomly selected markets. Data on sociodemographic characteristics of vendors and factors associated with contamination of fruits and vegetables were collected using a structured questionnaire. About 200 g of fruit and vegetable samples were processed for parasites using direct wet mount and modified Zeihl–Neelson staining techniques following standard protocols. All data were analyzed using SPSS version 23.Results: Among a total of 384 fruit and vegetable samples purchased from 112 vendors, 150 (39.1%) were contaminated with at least one species of parasite. Lettuce (56.4%) and mango (16.7%) were the most and the least commonly contaminated items respectively. Larva of Strongyloides species (13.5%) was the most frequently detected parasite followed by cysts of Entamoeba histolytica/E. dispar (12.8%). Contamination was more common in vegetables than fruits (AOR=2.968, p< 0.001). Fruits and vegetables purchased from vendors with untrimmed fingernails (AOR=1.966, p=0.006), directly delivered from farmers (AOR=1.883, p=0.040), displayed in bucket with water (AOR=2.676, p=0.017) and those displayed without washing (AOR=5.511, p< 0.001) were significantly associated with parasitic contamination.Conclusion: The level of parasitic contamination of fruits and vegetables in Bahir Dar city is of public health importance. Hence, the public health sector should create public awareness in order to reduce parasitic transmission via fruits and vegetables.Keywords: fruits, vegetables, contamination, parasite, market, Bahir Dar